Devices of quantum photonics fabricated using Nanoimprint Lithography - Li, Y (2023)
Planar-concave microcavities provide longitudinal and transverse optical confinement but are challenging to fabricate. This work reports a new method to fabricate a more scalable monolithic planar-hemispherical cavity using polymers and the deposition of metal mirrors. The FIB-milled stamp with hemispherical features serves as the foundation for the nanoimprint lithography (NIL). The feature size ranges from radii of curvature of 2µm to 10µm. The surface roughness of the feature is as low as 0.62 nm, measured by atomic force microscopy. Characterization of the optical microcavity reveals clear and Laguerre-Gaussian modes and the results exhibited good agreement with finite dimension time domain simulations. The resonance peak could be reliably controlled through tailored fabrication design, thereby enabling the cavity’s adaptation to a specific single emitter. These cavities are well-suited for quantum optics applications, including the detection of individual atoms and the efficient generation of single photons. The cavity used for emittercavity coupling has a mode volume of 0.098 V/λ 3 and resonance results in a decay time reduction exceeding a factor of 2; it is evident that Purcell enhancement has occurred, opening exciting opportunities for further research in this field.